2017
DOI: 10.1097/ta.0000000000001444
|View full text |Cite
|
Sign up to set email alerts
|

Results of a multicenter prospective pivotal trial of the first inline continuous glucose monitor in critically ill patients

Abstract: Diagnostic study, level I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
0
17
0
1
Order By: Relevance
“…In Europe, there are currently four CGM systems approved for intravenous use in hospitals: 1 ) GlucoClear by Edwards Lifesciences (Irvine, CA), 2 ) Glysure System by Glysure (Abingdon, U.K.), 3 ) Eirus by Maquet Getinge Group (Rastatt, Germany), and 4 ) OptiScanner 5000 by OptiScan (Hayward, CA); in addition, there is one CGM system approved for subcutaneous use in hospitals: Sentrino by Medtronic (Northridge, CA). Two CGM systems are FDA-approved for use in U.S. hospitals: GlucoScout (International Biomedical, Austin, TX) and recently the OptiScanner 5000 (83,90).…”
Section: Cgmmentioning
confidence: 99%
“…In Europe, there are currently four CGM systems approved for intravenous use in hospitals: 1 ) GlucoClear by Edwards Lifesciences (Irvine, CA), 2 ) Glysure System by Glysure (Abingdon, U.K.), 3 ) Eirus by Maquet Getinge Group (Rastatt, Germany), and 4 ) OptiScanner 5000 by OptiScan (Hayward, CA); in addition, there is one CGM system approved for subcutaneous use in hospitals: Sentrino by Medtronic (Northridge, CA). Two CGM systems are FDA-approved for use in U.S. hospitals: GlucoScout (International Biomedical, Austin, TX) and recently the OptiScanner 5000 (83,90).…”
Section: Cgmmentioning
confidence: 99%
“…Many of the devices reported in peer-reviewed literature (using different probe location sites and measurement techniques) fail to meet the mean absolute relative difference (MARD) point accuracy standard adopted by a previous consensus panel [ 54 ]. One exception is the Optiscanner® (OptiScan Biomedical Corporation, Hayward, CA, USA), which has been reported to have MARD < 10% [ 53 , 55 ], although other consensus requirements for CGM devices were not met or not reported. Importantly, comparisons, including MARD and Clark error grids, are based on evaluation of differences in values at a single time point, and do not take the trend factor into account.…”
Section: Moving Forward … and How To Keep The Industry On Board?mentioning
confidence: 99%
“…An advantage the EIRUS CGM has over other CE-marked CGM systems [31,32] is that its microdialysis sensing method does not require aspiration of blood across an ex-vivo glucose sensor. Systems that require aspiration of blood will be more prone to failure from inability to aspirate blood from the catheter due to biofilm, thrombus, or position of the catheter against the venous/arterial wall [33][34][35][36][37]. Although the EIRUS CGM demonstrated a MARD of 15.33% in the treated group, a recent clinical study done over a longer period in cardiac surgery patients demonstrated a MARD of 6.5% across 514 paired samples [23].…”
Section: Discussionmentioning
confidence: 99%